(untitled) (Bangladesh Pharmaceutical Journal, 2016)
Lower respiratory tract infections (LTRIs) are responsible for the vital causes of morbidity and mortality in all ages. In recent years, antibiotic resistance among respiratory pathogens is increasing emergently. The present study aimed to find out the bacterial etiology of LRTIs in Bangladesh and to update the clinicians about the current scenario of antibiotic resistance in lower respiratory tract infections. A total 64 bacterial pathogens from 100 patients with LRTIs were isolated from sputum specimens from a teaching hospital in Savar, Bangladesh between July- 2014 to June- 2015. The sputum specimens received within this year were subjected to analysis with microscopy, culture and susceptibility testing using conventional bacteriologic methods. Out of 100 processed sputum samples 64 (64%) cases had established bacterial etiology. Staphylococcus aureus (57.81%) was found to be the predominant organism in LRTIs followed by Streptococcus pneumonia (25%), Klebsiella and Pseudomonas species. Males (64.06%) were found to be more susceptible to LRTIs than that of females (35.93%). In antimicrobial susceptibility testing, grampositive organisms showed maximum sensitivity to imipenem (94.6%), meropenem (97.3%) and cefotaxime (75%). The resistance pattern varied for different organisms. Staphylococcus aureus isolates were mostly resistant to amoxicillin and ceftazidime (89.2%), whereas, Streptococcus pneumonia was to ceftazidime, amoxicillin and cotrimoxazole (81.2%). In case of gram negative isolates, Klebsiella sp. was mostly resistant to ceftriaxone, ceftazidime and amoxicillin (100%). Escherichia coli were resistant to amoxicillin, cotrimoxazole and vancomycin (100%). Therefore, appropriate identification of the causative organisms and their antibiotic resistance is crucial for right choice of antibiotic therapy in LRTIs. Bangladesh Pharmaceutical Journal 19(1): 85-91, 2016